Pemberdayaan Mualaf Pasca Konversi di Mualaf Center Yogyakarta - Abdillah, Arafat Noer (Universitas Muhammadiyah Magelang, 2020)
Converts in strengthening their diversity need moral and social support. This is based on the commitment and consequences of converts after conversion that are vulnerable to conflict and terror on the part of the family. Several studies that discuss the issue of converts focus more on the process of religious conversion. While converts who get terror or threats from the family need special empowerment with the aim of giving the right to freedom of religion. Therefore, the researcher will discuss the problem of converts after conversion and the role of the Yogyakarta Center for converts as religious institutions in fostering and providing decent living rights for converts. This study uses a psychological approach to religion and the theory of religious empowerment. The research method used is descriptive-qualitative by taking a closer look at the life of the informant so that it is easier to follow the flow of his life. Data collection includes participatory observation, interviews, questionnaires, and documentation. Data analysis was performed using data reduction procedures, data presentation and data verification using the triangulation method, and drawing conclusions. The results showed: 1) Converts get terror and termination of relations with family after the shahada. 2) Yogyakarta Mualaf Center provides moral and legal assistance in assisting post-shahadah converts with the aim of assisting the process of religious consolidation and providing post-shahada religious freedom of rights in terms of economic, independence of life, save house, and legal protection.